Pengujian kadar iodium total dalam urin dengan metode destruksi basah dan destruksi kering - Iswani S Iswani S (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Total iodine contents in the urine samples were directly tested with and without destruction using Ion Selective Electrode (ISE) method. The dry destruction was carried out with volume variation of 0.5 M NaOH solution and wet destruction was done with 4 ml of concentrated H2504 and 1 ml of concentrated HNO3 mixture, followed by volume variation of 1% p-aminophenol solution and temperature to reduce 103- form to form. The Chloride ion contents were also determined using technique. It was found that the optimum of NaOH amount, the optimum of 1% p-aminophenol and temperature (wet digestion) was 2 ml, 12 ml, and 60Â°C respectively. The chloride ion contents in 6 urine samples were in the range of 2373-4495 ppm and didn't interfere on r determination. The total r contents in the six samples without destruction,using wet and dry destructions were in the range of 280-392 ppb, 291-505 ppb and 306-516 ppb respectively. The t-test showed that the total Iodine content in urine samples with and without destructions was significantly different.Key words: Iodine - urine - ISE method - wet and dry destruction - chloride